Excavation Slopes Stability Analysis with Cracked Soil in the Construction of the Serang – Panimbang Toll Road (STA 54+625) Under Maximum Rainfall Condition - Purnamayoga, Wahyu; Saputra, Trihanyndio Rendy; Maulana, Mahendra Andiek; Winurseto, Wahyu Supriyo (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Construction of the Serang-Panimbang toll road requires deep excavation in several places finishing grade which then forms a roadside slope. Slope stability analysis is very critical in slope design so that infrastructure assets can be managed and maintained. The surrounding infrastructure may sustain damage if the slope is unstable. Rainfall is one of the most important triggers for landslide occurrence. In general, the effects of precipitation infiltration on slopes can cause changes in soil suction and positive pore water pressure, increase soil unit weight, and decrease soil shear strength. If cracked soil is found, the process of rain infiltration will be accelerated. It starts with small cracks and then turns into deep cracks, indicating the possibility of landslides, and the longer the landslide surface becomes, the more the slope will slide. This research discusses the effects of cracked soil and precipitation on slope stability. A slope stability analysis was performed using the Finite Element Method (FEM) and the cracked soil was modelled as a thin weak layer. The results showed that the safety factor decreased from 1,891 in the initial condition to 1,471 (before rain) and 1,441 (after rain) in the worst conditions.